Breast ultrasound in females 35 years old and below at a tertiary referral academic center in Cape Town, South Africa: indications and outcomes analysis, a retrospective quantitative study - Juggath, Nitin (Division of Radiology, 2024)
Title: Breast ultrasound in females 35 years old and below at a tertiary referral academic center in Cape Town, South Africa: indications and outcomes analysis, a retrospective quantitative study. Background A high number of patients are referred to our resource limited tertiary institution for specialty breast imaging. Despite the accepted application of ultrasound in young women with focal signs/symptoms, there are sparse outcomes data to validate its use in this clinical setting for certain indications and no prior study done at our facility. Objectives To decrease morbidity and expenditure related to breast imaging in young women by correlating clinical predictors for worrisome or benign findings, thus allowing refinement of referral criteria. Methods Ultrasounds performed on females below 35 years old in a 1-year period between 1 st March 2019-1 st March 2020 at Groote Schuur Hospital were retrospectively analyzed. Evaluation of the reports stored on the hospitals PACS system and review of the histological diagnosis of biopsies-if performed, from the NHLS. Clinical data and indication for referral was assessed and imaging results were categorised as either positive or negative. Positive findings were subcategorized into benign breast disease, breast abscess or malignancy. Results 352 breast ultrasound studies were performed. 65% were palpable mass referrals, and one-third were referred without any palpable mass or focal breast pain. 67% of the studies had a positive imaging result and 33% had a negative result. 214 were classified as benign breast disease, 11 as breast abscesses and 12 were malignant. Conclusions Majority of disease encountered was benign breast disease. Most referrals were appropriate and predominantly for a palpable mass. One-third of studies were inappropriately referred, adding to the burden on an already strained specialty center. Keywords Benign breast disease, breast abscess, malignancy, palpable mass, focal breast pain.